External And Internal Challenges to Industry 4.0 Implementation - Magdalena GĘBCZYŃSKA (Communications of International Proceedings, 2021)
Industry 4.0 is the process of streamlining and optimising production and other business processes and procedures using modern technologies. The fourth industrial revolution is changing the way industrial companies operate towards decentralised production. The implementation of Industry 4.0 solutions in individual entities differs due to the challenges and barriers resulting from the specificity and capabilities of these organizations. This study focuses on identifying which of the challenges related to the Fourth Industrial Revolution, selected on the basis of the critical literature analysis, are the most significant when implementing Industry 4.0 solutions. The aim of the study is to analyse these factors from the point of view of Polish small and medium manufacturing enterprises, based on their experiences to date. The selected challenges were divided into two groups: external and internal challenges.
Keywords: Industry 4.0; challenges; digitalization; SMEs